Covid-19 Pandemic And Its Likely Effect On Economic Development: An Opinion Survey of Professionals - Kumar, Atul; Gawande, Amol; Brar, Vinaydeep (Future Science / FSH-PH Publications, 2021)
The air is full of pessimism. The impact of Covid-19 has been anticipated as more awful than the Great Depression of 1930. Consistently analysts and agency reports are plunging into new bottoms of a tumbledown in economic activities. Indian economy, however, has a somewhat slightly different story to tell at this hour of crisis. The silver lining for the Indian economy originates from a lofty fall in crude oil costs from around 70 per barrel to a record multi-year low of 22 per barrel. They have ascended to levels of around 40 per barrel over the most recent months. This benefit increases can somewhat balance the immediate misfortunes due to Covid-19. Simultaneously, dreams like a 5 trillion economy no longer look even a distant chance. This article checks out the possible effect of Covid-19 on Indian economic development through a survey of 400 professionals the nation over.